A New Monolayer B4C4 with Robust Stability and Excellent Performance for Spontaneous Water Splitting Under Visible Light. Issue 6 (21st April 2021) - Li, Lin; Li, Xiaowei; Zhang, Qiuyu; Zhu, Dongyang; Li, Xiaoyu; Zhang, Yihe
Abstract: The nature of new monolayer boron carbides (B4 C4 ) and their photocatalytic performance for spontaneous water splitting are investigated using first‐principles calculations. It is interesting to find that B4 C4  has a special puckered surface similar to pure borophene and exhibits robust mechanical stability even at extremely high temperature in the molecular dynamics simulation. Its elastic constant in a direction is close to the superstar graphene in 2D materials. Moreover, B4 C4 also meets two necessary principles as a photocatalyst, it has proper valence and conduction band positions and a proper indirect bandgap. The optical absorption edge is about 525 nm corresponding a larger range of visible light adsorption than that of g‐C3 N4 . Additionally, the carrier mobilities are estimated to be about 800 cm 2  V −1  s −1 of the electron and 40 000 cm 2  V −1  s −1 of the hole which shows its excellent photocatalytic performance. Further calculations demonstrate that the H2 O molecule can be stably adsorbed on B4 C4 sheet, only a smaller activation energy is needed and the water splitting can be carried out spontaneously. The nanoribbon structures still maintain good performances for practical applications. Generally speaking, the new monolayer B4 C4 is an efficient and promising photocatalyst toward overall water splitting proved by these calculation results. Abstract : In this work, a new monolayer semiconducting boron carbide is designed and it is found that it has robust stability and excellent performance for spontaneous water splitting under visible light. Additonally, the nanoribbon structures still maintain good performance for practical applications. Their superior performance may allow them to surpass the traditional photocatalysts and become a new generation of catalytic material.